Effects of Group-Play Moderate to Vigorous Intensity Physical Activity Intervention on Executive Function and Motor Skills in 4- to 5-Year-Old Preschoolers: A Pilot Cluster Randomized Controlled Trial - Bai, Jing; Huang, Heqing; Ouyang, Huahong (Frontiers in Psychology, 2022)
The aim of the present study is to examine the effect of a group-play intervention on executive function (EF) in preschoolers. This group-play intervention was integrated moderate to vigorous physical activity and cognitively loaded exercise to promote EF in preschoolers. An 8-week group-play MVPA intervention program consisted of a serial of outdoor physical and cognitively-loaded games, was designed to improve preschoolers’ EF. This intervention program was implemented in group-play form, and conducted by teachers who received standardized training before the intervention. Two class of 2nd grade preschoolers (N = 62) were randomly allocated to experimental (n = 30, Mage = 4.16, SD = 0.285) and control (n = 32, Mage =4.7, SD = 0.432) groups. The intervention group received the intervention three times a week, while the control group exercised as usual in preschool. Before, in the middle of and after the intervention, 10-meter running, Standing broad jump, Throwing, Body flexion, Balance beam, and Skip jump were assessed as tests of motor skills. In addition, three components of EF were measured separately before, in the middle of, and after the intervention, with Inhibitory Control was assessed by using Silly Sound Stroop task, Working Memory was tested using Empty House task, and Shifting was assessed using Dimensional Change Card Sorting Task. Although both groups showed increasing trend in terms of motor skills and EF during the intervention, the increasing amounts of intervention group was significantly higher than the control group. The findings of the present study suggested that the group-play intervention has positive effects on aspects of EF in addition to motor skills in preschoolers.